Linguistic disorders and pathologies : an international handbook - Blanken, Gerhard, 1954-; Dittmann, Jürgen, 1947-; Grimm, Hannelore, 1940-; Marshall, John C., 1939-; Wallesch, Claus-Werner, 1953- (Handbücher zur Sprach- und Kommunikationswissenschaft,, 1993)
This handbook is geared towards the following aims: Reviewing the state of research on disordered language perception and production in adults and children. Describing and discussing present attempts at modelling human language processing by using linguistic disorders and pathologies as a data base. Presenting diagnostic and therapeutic concepts. Pointing out gaps and inconcistencies in current knowledge and theories. In bringing together knowlegde of different sources and disciplines under a common roof, the editors have achieved a comprehensive overview of the state of the art in the field of language pathology. Because of the diversity of the disciplines contributing to this scientific field, the chapters differ clearly in theories and methodologies. Yet this handbook represents a clear and common interdisciplinary contribution to linguistic disorders and pathologies and, furthermore, demonstrates the amount of interdisciplinary interaction still required. We chose this title in order to encompass as broadly as possible abnormalities and alterations of language perception, comprehension and production in adults and children, including nonpathological disorders. This handbook will be of interest to anybody involved with disordered language and/or language and speech disturbances, such as linguists and psychologists working in related research areas or teaching related subjects, scientists analyzing and modelling linguistic and cognitive processes (e.g. in Cognitive Psychology, Psycholinguistics, Neurolinguistics, Neuropsychology, Behavioural Neurology, Artificial Intelligence Research, and Cognitive Science), clinicians dealing with aquired or developmental language disorders, and speech pathologists and therapists. Besides presenting the state of the art, the handbook provides rich bibliographical information for research workers, clinicians, and advanced students.